2018
DOI: 10.20944/preprints201811.0410.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Representations of Natural Hazard Risk in Swiss Mountain Regions

Abstract: The term "risk" is connoted with divergent meanings in natural hazard risk research and the practice of risk management. Whilst the technical definition is accurately defined, in practice, the term "risk" is often synonymously used with "danger". Considering this divergence as a deficiency, risk communication often aims to correct laypersons' understanding. We suggest in reference to Breakwell (2001) to treat the variety of meanings as a resource for risk communication strategies instead. However, there is no … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…With respect to general weather information sources, there is very limited research available in the Swiss context. In her thesis on risk awareness and preparedness in Swiss natural hazard risk management, Maidl () found that the most common means to get informed about natural hazards is to follow weather forecasts in popular media such as radio, television and newspapers, followed by websites and mobile apps. More proactive forms such as attending information events or public discussions are less frequently used and social media appeared to be the least useful media (data on the availability and usage of 20 different means was collected) (Maidl, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to general weather information sources, there is very limited research available in the Swiss context. In her thesis on risk awareness and preparedness in Swiss natural hazard risk management, Maidl () found that the most common means to get informed about natural hazards is to follow weather forecasts in popular media such as radio, television and newspapers, followed by websites and mobile apps. More proactive forms such as attending information events or public discussions are less frequently used and social media appeared to be the least useful media (data on the availability and usage of 20 different means was collected) (Maidl, ).…”
Section: Discussionmentioning
confidence: 99%
“…In her thesis on risk awareness and preparedness in Swiss natural hazard risk management, Maidl () found that the most common means to get informed about natural hazards is to follow weather forecasts in popular media such as radio, television and newspapers, followed by websites and mobile apps. More proactive forms such as attending information events or public discussions are less frequently used and social media appeared to be the least useful media (data on the availability and usage of 20 different means was collected) (Maidl, ). In Germany, Kox and Thieken () found that slightly fewer people use weather forecasts daily (69.4%) compared to this study and that traditional mass media are still the primary source of weather information (in order of decreasing usage: TV, radio, websites, apps, newspapers, SMS/emails).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit to the approach is the assumption that the opportunity to be heard by authorities leads to Swiss citizens feeling that they are valued as actors in the development of new understandings, decisions and institutional capacities. Although the Swiss system provides opportunities for direct input into environmental planning decisions, the system has been criticised by some commentators as lacking effective ongoing mechanisms for all individuals to shape specific local outcomes (Höppner et al 2012;Home et al 2014;Inch 2015;Maidl and Buchecker 2019).…”
Section: The Swiss Deliberative Democratic Systemmentioning
confidence: 99%